Penerapan Edukasi Respiratory Muscle Stretching Untuk Meminimalkan Defisit Pengetahuan Pada Pasien Asma Bronkial: Studi Kasus - Feri, Jhon; Soewito, Bambang; Cindi, Paula (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2023)
Background: Bronchial asthma is a chronic disease of the airway that can be suffered by all age groups, symptoms that appear such as difficulty breathing or shortness of breath, chest pain, coughing and wheezing characterized by inflammation or narrowing of the airway due to intrinsic factors, extrinsic factors and mixed factors. One of the causes of recurrence of bronchial asthma is a knowledge deficit that can be increased through health counseling. Method: The type of research used is descriptive research with a case study approach on both subjects conducted on April 9-11, 2023 on subject I while subject II on April 15-17, 2023, research data was taken using pre-test and post-test questionnaire sheets, interviews, descriptive analysis and presented narratively. Results: After the implementation of nursing, the application of respiratory muscle stretching education through video media in subject I increased knowledge from 50% to 100% while subject II from 30% to 80%. Conclusion: The results showed that the application of respiratory muscle stretching education was effective in increasing patient knowledge about bronchial asthma.